2016
DOI: 10.1073/pnas.1607411113
|View full text |Cite
|
Sign up to set email alerts
|

Structural conservation in the template/pseudoknot domain of vertebrate telomerase RNA from teleost fish to human

Abstract: Telomerase is an RNA-protein complex that includes a unique reverse transcriptase that catalyzes the addition of single-stranded telomere DNA repeats onto the 3′ ends of linear chromosomes using an integral telomerase RNA (TR) template. Vertebrate TR contains the template/pseudoknot (t/PK) and CR4/5 domains required for telomerase activity in vitro. All vertebrate pseudoknots include two subdomains: P2ab (helices P2a and P2b with a 5/6-nt internal loop) and the minimal pseudoknot (P2b-P3 and associated loops).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 75 publications
0
32
0
Order By: Relevance
“…A direct correlation between pseudoknot stability and telomerase activity was demonstrated by thermodynamic analysis, through the use of nucleotide substitutions and compensatory mutations (157). Biochemical, mutational, and structural studies of yeast and medaka fish pseudoknots have revealed a conserved structure and confirmed the importance of the base triples for pseudoknot stability and telomerase function (Figure 3 a ) (17, 127, 147, 163, 171). A recent structure of the Tetrahymena pseudoknot revealed a more limited set of base triples, explaining in part its lower stability (Figure 3 a ) (18, 69).…”
Section: Telomerase Rna Domain Structuresmentioning
confidence: 66%
“…A direct correlation between pseudoknot stability and telomerase activity was demonstrated by thermodynamic analysis, through the use of nucleotide substitutions and compensatory mutations (157). Biochemical, mutational, and structural studies of yeast and medaka fish pseudoknots have revealed a conserved structure and confirmed the importance of the base triples for pseudoknot stability and telomerase function (Figure 3 a ) (17, 127, 147, 163, 171). A recent structure of the Tetrahymena pseudoknot revealed a more limited set of base triples, explaining in part its lower stability (Figure 3 a ) (18, 69).…”
Section: Telomerase Rna Domain Structuresmentioning
confidence: 66%
“…Although NMR spectroscopy has historically been used to determine structures of relatively small RNAs that typically comprise fewer than 60 nucleotides [67,68,69,70,71,72,73,74,75], the above studies have shown that structures can be probed by NMR spectroscopy in RNAs comprising up to 688 nucleotides. When used in combination with cryo-electron microscopy (cryoEM) or small-angle X-ray scattering (SAXS), 3D structural information can be obtained for relatively large protein:RNA complexes [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach was recently used to model the t/PK of medaka fish ( Orzyis lapites ), which has the smallest vertebrate TER [46]. This structural study of medaka pseudoknot domains showed that the tertiary stem-loop interactions are identical to human TER except it lacks a single nt bulge near the stem-stem junction, the predicted 6 nt bulge-loop is actually a 5 nt loop with the same structure as in hTER, and the adjacent predicted single-strand region forms a small hairpin that stacks on the adjacent helix [18]. Based on the model structures of the medaka and human t/PK and the locations of TER elements in Tetrahymena , models of medaka and human TERT in complex with the t/PK were presented (Figure 2e).…”
Section: Ter Structure and Assembly With Tertmentioning
confidence: 99%
“…The smFRET data of human TERT-TER complexes (discussed above) with primer bound (stalled) and actively synthesizing DNA showed three different positions of the pseudoknot fold relative to the template [47]. The authors propose that the pseudoknot moves during the telomere repeat synthesis cycle (pseudoknot tracking model); however, since they assumed a rigid structure for TERT in their Rosetta modeling they also suggest that the PK fold motion stabilizes the alternative conformation of TERT CTE proposed by Wang [18]. Most recently, a comprehensive mutational screen of TERT identified a ssDNA retention surface (SRS) within the CTE (Figure 3c), which is proposed to maintain placement of the 3′ end of the nascent DNA telomere repeat in the active site during template translocation, thereby contributing to repeat addition processivity [56].…”
Section: Mechanism and Dynamics Of Telomere Repeat Synthesismentioning
confidence: 99%
See 1 more Smart Citation